A sequent calculus for propositional temporal logic with time gaps - Alonderis, Romas (Lietuvos matematikos rinkinys, 2011)
A sequent calculus with Kripke semantics internalization for a propositional temporal logic with time gaps is introduced. All rules of the calculus are context-free and height-preserving invertible. Structural rules are admissible. The calculus is cut free and is proved to be complete.